Oral prenylation inhibition with lonafarnib in chronic hepatitis D infection: a proof-of-concept randomised, double-blind, placebo-controlled phase 2A trial. Issue 10 (October 2015) - Koh, Christopher; Canini, Laetitia; Dahari, Harel; Zhao, Xiongce; Uprichard, Susan L; Haynes-Williams, Vanessa; Winters, Mark A; Subramanya, Gitanjali; Cooper, Stewart L; Pinto, Peter; Wolff, Erin F; Bishop, Rachel; et al.
Summary Background Therapies for chronic hepatitis delta virus (HDV) infection are unsatisfactory. Prenylation is essential for HDV and inhibition abrogates HDV production in experimental models. In a proof-of-concept study, we aimed to assess the effect on HDV RNA levels, safety, and tolerability of the prenylation inhibitor lonafarnib in patients with chronic delta hepatitis. Methods In this phase 2A double-blind, randomised, placebo-controlled study, patients aged 18 years or older with chronic HDV infection were randomly assigned (3:1 in group 1 and 2:1 in group 2) to receive lonafarnib 100 mg (group 1) or lonafarnib 200 mg (group 2) twice daily for 28 days with 6 months' follow-up. Participants were randomised by random-number tables blocked in groups of four without stratification. Both groups enrolled six treatment participants and two placebo participants. Group 1 placebo patients received open-label lonafarnib as group 2 participants. The primary therapeutic endpoint was a decrease in HDV RNA viral titre in serum and the primary safety endpoint was the ability to tolerate the drug at the prescribed dose for the full 4-week duration, defined as drug discontinuation due to intolerance or grade 3/4 adverse events. This trial is registered with ClinicalTrials.gov, number NCT01495585. Findings Between Jan 19, 2012, and April 28, 2014, 14 patients were enrolled, of whom eight were assigned to group 1 and six were assigned to group 2. At day 28, compared with placebo, mean log HDV RNA declines from baseline were −0·73 log IU/mL in group 1 (95% CI 0·17–1·31; p=0·03) and −1·54 log IU/mL in group 2 (1·21–1·93; p<0·0001). Lonafarnib serum concentrations correlated with HDV RNA change (r2=0·78, p<0·0001). Model fits show that hepatitis B surface antigen (HBsAg) remained stable after a short pharmacological delay (0·75 days [SE 0·24]), lonafarnib effectiveness in blocking HDV production was greater in group 2 than in group 1 (0·952 [SE 0·06] vs 0·739 [0·05], p<0·001), and the HDV half-life was 1·62 days (0·07). There was no evidence of virological resistance. Adverse events were mainly mild to moderate with group 1 patients experiencing diarrhoea in three patients (50%) and nausea in two patients (33%) and in group 2 with all patients (100%) experiencing nausea, diarrhoea, abdominal bloating, and weight loss greater than 2 kg (mean of 4 kg). No treatment discontinuations occurred in any treatment groups. Interpretation Treatment of chronic HDV with lonafarnib significantly reduces virus levels. The decline in virus levels significantly correlated with serum drug levels, providing further evidence for the efficacy of prenylation inhibition in chronic HDV. Funding National Institute of Diabetes and Digestive and Kidney Diseases and National Cancer Institute, National Institutes of Health, and Eiger Biopharmaceuticals Inc.